Pekanbaru Sebagai Titik Nadi Perdagangan Zaman VOC: Penelitian - Nadia Ramona (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The city of Pekanbaru, nicknamed the city of fortune, has transformed into a center of economic growth and a prospective investment city in Indonesia, with developments in the oil, gas, and plantation sectors becoming the mainstay of trade. The rapid development of Pekanbaru is inseparable from its historical past; since ancient times, Pekanbaru has been a strategic trading point in the Strait of Malacca. Trading practices have been a mainstay to achieve the glory that has existed since ancient times in Indonesia, which has continued to grow since the era of the VOC in Indonesia. Maritime trade practices relate to the sea, which plays an important role in the political dynamics and society of Indonesia. The VOC, as a new power of the Western nations and the extension of Dutch rule in the East Indies since 1602, held power over almost all regions of Indonesia, including Pekanbaru, which was a trading hub in the past and has been the lifeblood of trade since the VOC era. The research method used is library research. Library research is an activity conducted by collecting information and data. The data or materials needed to complete this research come from libraries in the form of books. The colonial government's policies developed Pekanbaru effectively and made this city an administrative and trade center while not neglecting the historical roots of Pekanbaru itself, thus leading to the rapid development of Pekanbaru in trade activities.